Intramammary lymph node metastasis in a patient with ovarian carcinoma and a brief review of the literature - Demir, Lutfiye (Termedia Publishing House, 2012)
Metastasis from serous carcinoma of the ovary usually occurs in the subdiaphragmatic region. Metastasis to the breast and/or axillary-intramammary lymph node is very rare. It usually occurs in advanced disease, and it is important to distinguish a primary breast cancer from an ovarian cancer metastasis since the management of these two entities is totally different. Here we present a patient with metastasis to the breast and intramammary lymph nodes from ovarian serous carcinoma 25 months after diagnosis.